Nature-based approaches: a mixed methods study of facilitators and barriers to implementation in CAMHS - Siobhan B. Mitchell; Beth Chapman; Rachel Hayes; Hélène Bonnici; Hazel Banks; Silvana Mareva; Rebecca Hardwick (BMC, 2024)
Abstract Background There is growing evidence that spending time with or in nature can be beneficial for health and wellbeing. Emerging evidence suggests potential benefits for staff and service users in healthcare settings, yet little is known about how to put Nature-based approaches (NBAs) into practice within the Child and Adolescent Mental Health Services (CAMHS) setting. The CAMHS Goes Wild project in Southwest England aimed to explore the implementation of NBAs within CAMHS, examining staff attitudes and understanding to identify potential benefits and challenges through a mixed methods study. Methods The study involved three phases of data collection: an online survey with two waves, the first wave prior to the training, and the second four months post-training, and semi-structured interviews. Data collection was designed to fit around NatureWell training, attended by sixty-four CAMHS staff, which took place alongside the study. All participants were sampled from one NHS Trust and the study was open to both those who had attended the NatureWell training and those who had not. Data were synthesised to produce an understanding of staff attitudes towards NBAs and perceived barriers and facilitators to the implementation of this approach. Results Ninety-seven staff responded to the wave 1 survey and 57 responded to the wave 2 survey. Fourteen staff members were interviewed. Data synthesis generated three themes: Tension between the culture of CAMHS and NBAs (Theme 1) and the need for buy-in and governance support (Theme 2). Theme three described the potential benefits of NBAs for staff and service users in CAMHS and is presented in a separate paper. The first two themes are presented in this paper. Conclusions The implementation of NBAs in mental health service settings for CYP presents both significant challenges and opportunities. Our findings suggest multiple barriers to implementation, often in the form of organisational or cultural factors, such as the risk averse nature of the service. Our work also elucidates several potential facilitators which may address or mitigate some of these barriers. These potential enablers, such as harnessing the role of firsthand experience, warrant further exploration in the implementation of NBAs in CAMHS.